Alleviation of stuck wine fermentations using salt‐preconditioned yeast. Issue 3 (10th June 2014) - Logothetis, Stelios; Nerantzis, Elias T.; Tataridis, Panagiotis; Goulioti, Anna; Kannelis, Anastasios; Walker, Graeme M.
<x xml:space="preserve">Abstract</x> The influence of salt (sodium chloride) on the cell physiology of wine yeast was investigated. Cellular viability and population growth of three wine‐making yeast strains of Saccharomyces cerevisiae, and two non‐Saccharomyces yeast strains associated with wine must microflora (Kluyveromyces thermotolerans and K. marxianus) were evaluated following salt pre‐treatments. Yeast cells growing in glucose defined media exposed to different sodium chloride concentrations (4, 6 and 10% w/v) exhibited enhanced viabilities compared with nontreated cultures in subsequent trial fermentations. Salt 'preconditioning' of wine yeast seed cultures was also shown to alleviate stuck and sluggish fermentations at the winery scale, indicating potential benefits for industrial fermentation processes. It is hypothesized that salt induces specific osmostress response genes to enable yeast cells to better tolerate the rigours of fermentation, particularly in high sugar and alcohol concentrations. Copyright © 2014 The Institute of Brewing & Distilling